2022
DOI: 10.3390/foods11172601
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Functional Parameters of Fermented Milk Obtained from Goat Milk Fed with Broccoli and Artichoke Plant By-Products

Abstract: Large amount of vegetal by-products are generated during production and processing steps. Introducing silage from vegetable by-products into dairy goat feed would be of great interest from the point of view of reducing costs and supporting the circular economy. The aim of this research was to study the effect of 40% inclusion of silage broccoli by-products and artichoke plant by-products in the diet of Murciano-Granadina goats throughout the lactation to establish milk suitability for fermented milks productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The volatile composition of the samples was determined by headspace solid-phase microextraction (HS-SPME) in combination with gas chromatography coupled with mass spectrometry using the same conditions as previously reported [ 16 ]. A total of 6 g of sample was weighed, and NaCl (0.6 g) was added into a 40 mL vial with polypropylene caps and PTFE/silicone septa.…”
Section: Methodsmentioning
confidence: 99%
“…The volatile composition of the samples was determined by headspace solid-phase microextraction (HS-SPME) in combination with gas chromatography coupled with mass spectrometry using the same conditions as previously reported [ 16 ]. A total of 6 g of sample was weighed, and NaCl (0.6 g) was added into a 40 mL vial with polypropylene caps and PTFE/silicone septa.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a thermal treatment before the extraction process or enzymatic hydrolysis can increase fiber recovery from stems. This fiber is mainly characterized by 70% inulin, with a low amount of low-DM (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) pectin; it exhibits high or low viscosity, depending on whether a high or low shear rate is applied, as pseudoplastic material. The high amount of inulin, together with the presence of low-DM pectin and calcium (40 mg/g pectin), contribute to form rigid gels.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…In particular, the quality of the starting raw material and the selection of the extraction method are fundamental. A good solution to obtain stable and high-quality by-products is represented by the silage fermentation process, in which the increase of lactic acid bacteria (mainly Lactobacillus acidophilus and Bifidobacterium bifidum) can affect the content or release of nutrients and bioactives [19,26,29,30]. Over the years, to develop a real global circular-economy model able to minimize the environmental and economic impact, the application of green extraction methodologies represented a valid strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suitable for ruminant feed when it reached 200 days due to its superior microbial and nutritional composition. Muelas et al. (2022) added 40% broccoli by-product silage to a balanced ration of dairy goats over a long period, and showed that the milk produced by dairy goats fed with broccoli silage was suitable for yogurt and cheese fermentation and that mixing broccoli silage with balanced ration improved the antioxidant performance of dairy goats.…”
Section: Distribution Of Broccoli Resources and Utilization Of Stalks...mentioning
confidence: 99%